الإثبات في المنازعات الإدارية - - بن يونس محمد عبد الستار (جامعة المسيلة, 2021)
تعد مرحلة الإثبات من أهم المراحل التي تمر بها الدعوى الإدارية، نظرا للتفاوت بين مراكز الخصوم، على خلاف الدعوى المدنية التي تقوم بين خصمين متساويين، لذلك فإن تطبيق القواعد العامة للإثبات على الدعوى الإدارية ذات الطبيعة الخاصة والمتميزة عن المنازعات العادية، فيه تعسف على حقوق الطرفين في النزاع الإداري وعلى القانون الإداري. إن الإثبات في المواد الإدارية يتميز بطابع خاص، يتمثل في وجود الإدارة كطرف أساسي في الدعوى الإدارية، حيث أنها تتمتع بامتيازات السلطة العامة، وهذا ما يؤثر بشكل مباشر في الإثبات فيها، نظرا لمركز السلطة الإدارية في الإجراءات القضائية الإدارية. ولقد ترتب على ذلك وجود قواعد وإجراءات خاصة بالإثبات في المنازعة الإدارية تتعلق أهمها بسلطات القاضي الإداري، خاصة فيما تعلق بعبء الإثبات. إن إقامة الدليل في المنازعة الإدارية هو وسيلة للوصول إلى الحقيقة يقوم بها القاضي الإداري من واقع ما يعرض عليه من مستندات وأدلة إثبات، فلا يقتصر دور القاضي الإداري أثناء تقصيه للحقيقة على وسائل الإثبات المنصوص عليها في القانون فقط، إنما عليه أن يعتمد في حل المنازعة المعروضة أمامه على كل دليل يوصله إلى الحقيقة. الكلمات المفتاحية: الإثبات في المنازعات الإدارية، دور القاضي الإداري، عبء الإثبات، وسائل الإثبات. abstract: The stage of proof is one of the most important stages that the administrative case goes through, given the disparity between the centers of the litigants, unlike the civil case that is between two equal opponents. In administrative dispute and on administrative law. Evidence in administrative materials is characterized by a special character, represented by the presence of the administration as a primary party in the administrative lawsuit, as it enjoys the privileges of the public authority, and this directly affects the evidence in it, given the position of the administrative authority in administrative judicial procedures. This has resulted in the existence of rules and procedures for evidence in administrative disputes, the most important of which are related to the powers of the administrative judge, especially with regard to the burden of proof. The establishment of evidence in the administrative dispute is a means to reach the truth carried out by the administrative judge from the reality of the documents and evidence presented to him. In front of him on every evidence leads him to the truth. Keywords: Evidence in administrative disputes, the role of the administrative judge, burden of proof, means of proof.
Keywords: : الإثبات في المنازعات الإدارية، دور القاضي الإداري، عبء الإثبات، وسائل الإثبات.